Pengaruh Waktu Pertama Pemberian Makanan Pendamping ASI terhadap Status Gizi Bayi Usia 6 – 24 Bulan - Gracella Faustine; Arfiyanti Arfiyanti; Feda Anisah Makkiyah; Rahmah Huda Nurrizka (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2021)
Background. Malnutrition is a global problem with high morbidity and mortality rates. The fulfillment of adequate nutrition, especially in the early stage of life, is very important for growth and development. Early nutrition in a child’s life begins with exclusive breastfeeding which contains all the elements of nutrients needed. When breast milk is not sufficient to meet the nutritional needs of infants, specific nutritional interventions in the form of complementary foods are required. A review about the effect of the right time of complementary foods is needed to ensure optimal nutritional status. Objective. Analyzed the effect of timing of introduction to complementary foods on nutritional status in infants aged 6 – 24 months. Methods. A systematic literature review using PRISMA-P 2020 by reviewing studies obtained through databases such as Scopus, PubMed, and Google Scholar. Result. A total of 7 literatures were obtained with 5 literatures having significant results. The incidence of stunting is 1.21-13.3 times higher in complementary foods given at <6 months of age and 1.64-fold in >8 months. The incidence of underweight occurs 2.14 times in complementary foods given at the age of 4-5 months. The incidence of wasting has a 2.86-fold risk in complementary foods given at the age of 0-1 months. The risk of being overweight can occur 1.50-1.66 times in complementary foods given at less than 6 months. Conclusion. Early (<6 months) and late (>8 months) introduction to complementary foods has an effect on the incidence of stunting, underweight, wasting, and overweight in infants aged 6-24 months.Keywords: Malnutrition, Complementary Foods, Nutritional Status AbstrakLatar belakang. Malnutrisi merupakan permasalahan global dengan angka morbiditas dan mortalitas yang tinggi. Pemenuhan gizi yang tepat pada fase awal kehidupan sangat penting bagi proses tumbuh kembang. Pemberian gizi anak diawali dengan ASI ekslusif yang mengandung semua unsur zat gizi yang dibutuhkan bayi. Pada saat ASI tidak cukup untuk memenuhi kebutuhan gizi bayi, diperlukan intervensi gizi spesifik berupa MPASI. Peninjauan pengaruh waktu yang tepat pada pemberian MPASI diperlukan untuk menjamin status gizi anak yang optimal. Tujuan.Menganalisis pengaruh waktu pertama pemberian MPASI terhadap status gizi bayi usia 6 – 24 bulan. Metode.Tinjauan pustaka sistematis metode PRISMA-P 2020 dengan meninjau studi yang diperoleh melalui basis data Scopus, PubMed, dan Google Scholar. Hasil. Didapatkan total 7 literatur dengan 5 menunjukkan hasil signifikan pengaruh waktu pertama pemberian MPASI terhadap status gizi bayi usia 6 – 24 bulan. Kejadian stunting berisiko 1,21 – 13,3 kali lipat pada MPASI < 6 bulan dan 1,64 kali lipat pada MPASI >8 bulan. Underweight berisiko 2,14 kali lipat pada MPASI 4 – 5 bulan. Wasting berisiko 2,86 kali lipat pada MPASI 0-1 bulan. Risiko overweight terjadi 1,50 – 1,66 kali lipat pada MPASI <6 bulan. Kesimpulan. MPASI dini (<6 bulan) dan terlambat (>8 bulan) berpengaruh terhadap stunting, underweight, wasting, dan overweightKata Kunci: Malnutrisi, MPASI, Status Gizi